2001
DOI: 10.1007/s002960000094
|View full text |Cite
|
Sign up to set email alerts
|

Free radical changes in rat muscle tissue after exercise

Abstract: Intense exercise accompanied by a manifold increase in oxygen utilization over resting conditions has been shown to elevate the probability of the appearance of free radicals. One of the effects of free radicals appears to be the peroxidation of cell membrane lipids resulting in malondialdehyde formation, which is detrimental to cell function. A common method for the measurement of malondialdehyde involves a reaction with thiobarbituric acid. The aim of this study was to evaluate the influence of exercise on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…In the present study, we demonstrated that the 8-week exercise training in rats did not alter SOD, CAT and GPx activities in the kidney. These results are consistent with those of others, in which regular training was shown to have little eVect on renal, myocardial and hepatic anti-oxidant enzyme systems while a signiWcant up-regulation of antioxidant enzymes was demonstrated in skeletal muscles, which were actively involved in exercise (Ji 1993;Hong and Johnson 1995;Benderitter et al 1996;Oh-ishi et al 1997;Liu et al 2000;Pohlman and Harlan 2000;Arslan et al 2001;Gunduz et al 2004). The results suggest that exerciseinduced oxidative stress could be a prominent damaging factor in organs actively involved in exercise, such as skeletal muscle and, thus, adaptive processes in these tissues might require increased activity of antioxidant enzymes.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In the present study, we demonstrated that the 8-week exercise training in rats did not alter SOD, CAT and GPx activities in the kidney. These results are consistent with those of others, in which regular training was shown to have little eVect on renal, myocardial and hepatic anti-oxidant enzyme systems while a signiWcant up-regulation of antioxidant enzymes was demonstrated in skeletal muscles, which were actively involved in exercise (Ji 1993;Hong and Johnson 1995;Benderitter et al 1996;Oh-ishi et al 1997;Liu et al 2000;Pohlman and Harlan 2000;Arslan et al 2001;Gunduz et al 2004). The results suggest that exerciseinduced oxidative stress could be a prominent damaging factor in organs actively involved in exercise, such as skeletal muscle and, thus, adaptive processes in these tissues might require increased activity of antioxidant enzymes.…”
Section: Discussionsupporting
confidence: 94%
“…The available data suggest that regular training reduces the capacity of some tissues to release ROS and leads to adaptation of antioxidative mechanisms, which Wnally may contribute to a limitation of exercise-induced oxidative damage (Niess et al 1999). It has been reported that regular training could increase antioxidant defense capacity and, therefore, could protect against cellular stress in the working skeletal muscle, whereas it has little eVect on the hepatic and myocardial antioxidant enzyme system (Benderitter et al 1996;Arslan et al 2001;Pohlman and Harlan 2000;Pedersen and HoVman-Goetz 2000;Rus et al 2003). The variability of response of diVerent tissues to exhaustive and regular exercise depends on their variable past exposures to oxidative stress and/or to their intrinsic oxidant status (Ji 1996(Ji , 2002Liu et al 2000).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Mitochondria are the source and target of ROS because complexes I and III of the electron transport chain are the main sites of mitochondrial superoxide production [ 38 , 60 ] . The magnitude of changes in exercise induced ROS depends on the type of muscle fi bre [ 7 ] as cellular Ca 2+ overload activates the degradation of muscle proteins and membrane phospholipids via Ca 2+ dependent proteolytic and phospholipolytic pathways [ 6 ] . Ca 2+ overload results in the uptake of Ca 2+ into mitochondria [ 99 ] , reduces mitochondrial capacity to synthesize ATP and causes damage of mitochondrial membranes.…”
Section: Exhaustive Exercise and Rosmentioning
confidence: 99%